Autonomous Navigation for an Unmanned Aerial Vehicle by the Decomposition Coordination Method - Chaimaa Jihane; Hala El Ouarrak; Mohamed Mestari; Mostafa Rachik (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
This paper introduces a new approach for solving the navigation  problem  of Unmanned Aerial  Vehicles (UAV) by studying its rotational and  translational dynamics and  then solving the nonlinear model by the Decomposition  Coordination method. The objective is to reach a destination goal by the mean of  an autonomous  computed   optimal path calculated   through optimal control sequence. Solving such complex systems often requires a great  amount of computation. However, the approach considered herein is based on  the Decomposition Coordination principle, which allows the nonlinearity to be treated at  a local level, thus offering a  low computing time. The stability of the method is discussed with sufficient conditions for convergence. A numerical application is given in consolidation  the theoretical results.